Pengaruh Supervisi Akademik, Kepemimpinan Kepala Sekolah, dan Iklim Sekolah terhadap Kinerja Guru Sekolah Dasar - Akbar, Hastian Artifan; Abdullah, Ghufron; Ginting, Rosalina Br. (PGRI Kota Semarang, 2024)
This study aims to describe and analyze: Teacher performance in Elementary School Sekbin 4 and 7, Brebes District, Brebes Regency (1) The Influence of Academic Supervision on Teacher Performance (2) The Influence of Principal Leadership on Teacher Performance (3) The Influence of School Climate on Teacher Performance (4) The Influence of Academic Supervision, Principal Leadership and School Climate on Elementary School Teacher Performance in Sekbin 4 and 7, Brebes District, Brebes Regency. The background of this study is the fact that the performance of elementary school teachers in Sekbin 4 and 7, Brebes District, Brebes Regency is low. Rare Academic Supervision and Principal Leadership, and School Climate are factors that influence low teacher performance. This study uses a quantitative research approach and ex post facto research type. The population of the study was all elementary school teachers in Sekbin 4 and 7, Brebes District, Brebes Regency, totaling 190 teachers and a research sample of 129 teachers. The analysis of this study includes normality test analysis, linearity test, multicollinearity test, and homogeneity test. Hypothesis testing includes simple regression test and multiple regression test with α = 0.05. The results of the study indicate that: (1) there is an influence of academic supervision on teacher performance which is stated by the simple regression equation Ŷ = 27.365 + 0.781X1. with a contribution of 89.6%; (2) there is an influence of principal leadership on teacher performance which is stated by the simple regression equation Ŷ = 69.564 + 0.290X2 with a contribution of 34.6%; (3) there is an influence of school climate on teacher performance expressed by a simple regression equation Ŷ = 53.808 + 0.412X3 with a contribution of 43.8% and (4) there is an influence of academic supervision, principal leadership and school climate on teacher performance expressed by a multiple regression equation Ŷ = 30.327 + 0.860 X1 + -0.089 X2 + 0.028 X3 with a contribution of 91.1%. The researcher's suggestions are: (1) the education office holds training activities related to improving teacher performance.; (2) the principal should always conduct supervision in accordance with the provisions and procedures, strive to be a good leader and create a conducive school climate so that teachers feel comfortable and more enthusiastic in working so that it will affect the increase in teacher performance.; and (3) teachers need to maintain harmonious relationships between school personnel and support each other so that the school climate becomes conducive.